PEMBUKTIAN SEDERHANA DALAM PUTUSAN PERKARA NOMOR 48/ PAILIT/ 2012/ PN. NIAGA. JKT. PST ANTARA PT. PRIMA JAYA INFORMATIKA DENGAN PT. TELEKOMUNIKASI SELULAR - Irhamni Irhamni; Nova Yarsina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Bankruptcty is a general confiscation of all wealth management and bankruptcy debtor completion conducted by curator under the supervisory judge as provided in this Act. Differences decision is often the case in the simple proof in bankruptcy cases and one case, namely case of the PT. Telekomunikasi Selular against PT. Prima Jaya Informatika make simple proof is not as easy as deciphering simple words. Pending the availability of criteria, one point of view, understanding, and same perception of the retail panel of judges at the court or the supreme court on the first floor and reconsideration of cassation in deciding a similar thing, so it can accelerate the course of the trial process. Application of a simple proof in bankruptcy at the commercial court decision Number: 48/ Pailit/ 2012/ PN.Niaga.Jkt.Pst should arrangement of limitations simple proof in the law, so that the parties or judges who examine and rule on cases of bankruptcy has clear boundaries so that the creation a rule of law.Keywords: Proof ; Simple Proof ; Bankruptcy